Singular/Plural contrasts: The case of Informational Object Nouns - Sutton, Peter R.; Filip, Hana (Proceedings of the Amsterdam Colloquium, 2019)
This paper brings together a number of different topics in semantics: the count/mass distinction, telicity, plurality, and cumulativity and distributivity. We focus on sentences containing Informational Object Nouns (IONs) such as statement and belief in constructions such as Alex’s/Alex and Billie’s statement(s)/belief(s) that p/that p and q). We observe that the interpretation of the ION in such constructions vis-` a-vis referring to a proposition/propositions or to an eventuality/eventualities is sensitive to whether the subjective genitive and the ION are singular or plural, and to whether the complement clause is simplex (p) or complex (p and q). We derive these patterns based on a theory of the mass/count distinction for IONs developed in Sutton and Filip (2019).